2021
DOI: 10.3389/fpsyt.2020.584907
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Comorbidities in Moroccan Patients With Breast Cancer

Abstract: Background: Breast cancer is the leading cause of cancer death in women worldwide with more than 1. 7 million new cases annually. Major advances have been made in the therapeutic management of this condition in many countries. However, neuropsychiatric disorders in patients with breast cancer constitute a significant concern due to their negative impact on patient's life and on the success of therapy itself.Methodology: In this study we aimed to evaluate psychological disorders in a population of 212 Moroccan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(17 reference statements)
0
4
1
Order By: Relevance
“…SCZ was the risk factor for overall breast cancer, ER+ breast cancer and ER-breast cancer. Interestingly, many observational studies have indicated that breast cancer is a risk factor for psychiatric disorders (24)(25)(26), but our MR analysis showed a reverse finding.…”
Section: Discussioncontrasting
confidence: 65%
“…SCZ was the risk factor for overall breast cancer, ER+ breast cancer and ER-breast cancer. Interestingly, many observational studies have indicated that breast cancer is a risk factor for psychiatric disorders (24)(25)(26), but our MR analysis showed a reverse finding.…”
Section: Discussioncontrasting
confidence: 65%
“…Among patients with cancer with different types of insurance, the DA level of self-funded patients with cancer was the highest, suggesting that better medical reimbursement can relieve some of the burden of medical costs on patients, thereby allowing them to focus on their illnesses 35. A study abroad also showed that patients with cancer with health insurance had lower levels of anxiety and depression 36. Therefore, the DA of patients with cancer without insurance should be better reduced.…”
Section: Discussionmentioning
confidence: 99%
“…35 A study abroad also showed that patients with cancer with health insurance had lower levels of anxiety and depression. 36 Therefore, the DA of patients with cancer without insurance should be better reduced.…”
Section: Open Accessmentioning
confidence: 99%
“…Psychological problems in patients with breast cancer should receive more attention [ 32 ]. Our results suggest that anxiety and depression were common in the NAC group of our patient cohort.…”
Section: Discussionmentioning
confidence: 99%